The impact of sector credit concentration indicator in calculating of the expected credit losses in accordance with IFRS (9) "An Analytical study on conventional banks listed on the Damascus Securities Exchange" (Damascus University Journal for the economic and Political sciences, 2023)
This paper investigates the impact of credit concentration indicator in calculating of expected credit losses in accordance with IFRS (9) based on the financial statements published during the period from December 31, 2018 to December 31, 2020.The descriptive and analytical approach followed in this paper using a sample of (9) banks represents the conventional banks listed on the Damascus securities exchange using panel data to test the paper hypothesis.The paper concluded that there is a significant negative impact of credit concentration indicator in calculating of expected credit loss in accordance with IFRS (9) for conventional banks listed on the Damascus Stock Exchange during the period studied.
Keywords: Credit Concentration Indicator; Expected Credit Loss